An Ecodevelopmental Framework for Engaging Diverse Youth in Foster Care and Their Families Into Technology-Based Family Intervention Research Trials - Folk, Johanna B.; Gill, Heman; Ordorica, Catalina; Rodriguez, Christopher A.; Holloway, Evan D.; Meza, Jocelyn; Tolou-Shams, Marina (Frontiers in Digital Health, 2022)
Family-based interventions delivered via telehealth are a promising mode for overcoming barriers to behavioral health treatment among youth in foster care and their families. There is a dearth of research, however, regarding effectiveness of these interventions for youth in foster care, who commonly exhibit complex behavioral health treatment needs. Clinical research in this area directly relates to equity in service access and quality for these youth and families, with numerous barriers and enabling factors to consider in order to improve engagement in clinical trials and bolster the evidence base. We present a framework to better understand the multi-systemic factors impacting youth and family engagement in clinical research on family-based telehealth interventions, drawing on relevant theory, including the bioecological model and ecodevelopmental theory. We also draw on our experiences conducting technology-based clinical research through the Family Telehealth Project, an evaluation of a brief family-based affect management intervention designed specifically for youth in foster care and their families, as a case example. Recommendations for promoting engagement in clinical research on family-based telehealth interventions with diverse youth in foster care and their families are provided.